The crosstalk of telomere dysfunction and inflammation through cell-free TERRA containing exosomes. Issue 8 (2nd August 2016) - Wang, Zhuo; Lieberman, Paul M.
ABSTRACT: Telomeric repeats-containing RNA (TERRA) are telomere-derived non-coding RNAs that contribute to telomere function in protecting chromosome ends. We recently identified a cell-free form of TERRA (cfTERRA) enriched in extracellular exosomes. These cfTERRA-containing exosomes stimulate inflammatory cytokines when incubated with immune responsive cells. Here, we report that cfTERRA levels were increased in exosomes during telomere dysfunction induced by the expression of the dominant negative TRF2. The exosomes from these damaged cells also enriched with DNA damage marker γH2AX and fragmented telomere repeat DNA. Purified cfTERRA stimulated inflammatory cytokines, but the intact membrane-associated nucleoprotein complexes produced a more robust cytokine activation. Therefore, we propose cfTERRA-containing exosomes transport a telomere-associated molecular pattern (TAMP) and telomere-specific alarmin from dysfunctional telomeres to the extracellular environment to elicit an inflammatory response. Since cfTERRA can be readily detected in human serum it may provide a useful biomarker for the detection of telomere dysfunction in the early stage of cancers and aging-associated inflammatory disease.